Implementation of the Use of Sopep Equipment During Bunkering on the MT Giat Armada 04 Ship - Krisna Aprillio Putra Nugroho; Elise Dwi Lestari; Natriya Faisal Rachman; Sutoyo (International Journal of Science and Environment (IJSE), 2026)
Marine pollution due to bunkering activities has become a serious problem along with the increase in tanker activity and operational risks. This study aims to analyze the implementation and effectiveness of the Shipboard Oil Pollution Emergency Plan equipment during bunkering on the MT Giat Armada 04 vessel. The study used a qualitative case study approach supported by quantitative data. The population was all crew members, with a purposive sample of 18 informants directly involved in bunkering activities. Data were collected through observation, semi-structured interviews, and Likert-scale questionnaires, then analyzed using data reduction, descriptive statistics, and triangulation. The results showed that the implementation of the SOPEP was classified as good with an average score of 3.84. The availability of equipment and crew understanding were adequate, but practical skills, compliance with PPE use, and the feedback system still needed to be improved. The study concluded that the SOPEP was effective in reducing the risk of oil spills during bunkering, but needed optimization through equipment maintenance, increased training frequency, and strengthened communication between crew and management.